Analisis Persepsi Mahasiswa Terhadap Pentingnya Pengelolaan Dokumen Digital Pribadi - Mutmainah, Shofa Destia; Sari, Anggita Amelia; Hapsari, Nabila Oktabrina; Nursyamsiah, Devita; Darmawan, Vira Anggita; Azzahra, Najwa Aulia; Diva, Diva; Kholis, Muhammad Husamuddin (Prisani Cendekia, 2025)
The rapid development of information technology has significantly transformed how university students manage their personal documents—from physical to digital formats. Despite this shift, many students still face challenges in managing digital documents systematically and securely. This study aims to examine students’ perceptions of the importance of personal digital document management in supporting academic and administrative activities. The research is grounded in digital literacy theory, the Theory of Planned Behavior, and document management principles as outlined in ISO 15489 and the Indonesian National Archives Regulation No. 26 of 2011. A descriptive quantitative method was employed, utilizing an online survey distributed to 32 active university students across Indonesia. The findings reveal that although the majority of respondents recognize the importance of digital document management, many lack the technical competencies necessary for effective implementation—such as structured file organization, consistent file naming, data backup, and information security. The study concludes that while students' attitudes are generally positive, their limited digital skills hinder consistent and reliable document management practices. Therefore, enhancing students’ digital literacy is essential to ensure efficient, secure, and accountable personal document management.